2014
DOI: 10.1186/1475-2840-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cardiovascular safety of saxagliptin in patients with type 2 diabetes mellitus: pooled analysis of 20 clinical trials

Abstract: BackgroundIt is important to establish the cardiovascular (CV) safety profile of novel antidiabetic drugs.MethodsPooled analyses were performed of 20 randomized controlled studies (N = 9156) of saxagliptin as monotherapy or add-on therapy in patients with type 2 diabetes mellitus (T2DM) as well as a subset of 11 saxagliptin + metformin studies. Adjudicated major adverse CV events (MACE; CV death, myocardial infarction [MI], and stroke) and investigator-reported heart failure were assessed, and incidence rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 49 publications
2
44
0
4
Order By: Relevance
“…26,27 There was no signal of fluid retention, weight gain, or heart failure with saxagliptin in the Phase 2 and Phase 3 development program. 28 Moreover, previous preclinical data and small studies with other incretin-based agents suggested potential improvement of left ventricular function, 26 but these data are inconsistent. Two preliminary reports of other studies in patients with DDP-4 inhibitors produced unanticipated findings that highlight potential mechanisms by which treatment with DPP-4 inhibitors could exacerbate heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 There was no signal of fluid retention, weight gain, or heart failure with saxagliptin in the Phase 2 and Phase 3 development program. 28 Moreover, previous preclinical data and small studies with other incretin-based agents suggested potential improvement of left ventricular function, 26 but these data are inconsistent. Two preliminary reports of other studies in patients with DDP-4 inhibitors produced unanticipated findings that highlight potential mechanisms by which treatment with DPP-4 inhibitors could exacerbate heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…While long-term studies are ongoing, combined analyses of shorterterm trials can provide some insights on possible CV actions of new treatments. In the case of DPP-4 inhibitors, pooled analyses of CV events in randomized phase II-III studies have been published for all molecules (38)(39)(40)(41)(42); all these analyses yielded risk estimates ,1, although differences from comparator groups were not statistically significant (Table 2). Data from different analyses are not comparable, because the definition of events and the trial entry criteria are heterogeneous.…”
Section: Pooled Analyses and Meta-analyses: Combining CV Outcome Studmentioning
confidence: 99%
“…Nevertheless, it seems relatively clear that young patients without CVD have a very low rate of heart failure, and saxagliptin does not increase the risk in this population. 18 Although there were only 74 total major cardiovascular events in a population of 8903 in this 20-study saxagliptin meta-analysis, the events were not adjudicated. The bulk of the patients in these trials were younger than 65 years of age, had diabetes for o5 years, and had no pre-existing CVD.…”
Section: Discussionmentioning
confidence: 98%